MODERN METHODOLOGICAL MODEL FOR TEACHING FOREIGN LANGUAGES IN PRESCHOOL EDUCATION - Choriyeva Xurmo (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This article examines a modern methodological model for teaching foreign languages in preschool institutions. The study highlights innovative approaches and pedagogical strategies aimed at developing linguistic competencies, communication skills, and cognitive abilities in young learners. Emphasis is placed on interactive methods, game-based learning, multimedia resources, and situational exercises that enhance children's motivation, speech activity, and practical language usage. The proposed methodological model provides preschool educators with effective guidelines for organizing engaging, developmentally appropriate, and productive foreign language lessons.